ANALISIS KEBIJAKAN PENDIDIKAN TERKAIT PENERAPAN MUATAN LOKAL DAN KETERAMPILAN SEBAGAI MATA PELAJARAN - Sugianti Sugianti; Santi Santi; Rositah Rositah (Institusi Agama Islam Negeri (IAIN) Bone, 2020)
Local content is one of the most important elements for education in Indonesia. Lokalcontent is a set of plans and arrangements regarding the objekctives, content, and learningmaterials compiled by education units according to the diversity of the potential of eachregion. This study is aimed to know: (1) Analisis of local content education policies in thecurriculum. (2) Teacher involvement in the application of local cantent and skills assubjects. The research method used in this study is a qualitative method with a descriptiveapproach to the study of documents/texts. Result of this study shows that:(1) Educationpolicy analysis becomes very important in the application of local content because itis supported by the curriculum. (2) The role of the teacher in the education systemholds full responsibility in the implementation of education for the success of theirstudents so that teacher involvement is important in the application of local contentand subject skills.